ASCARIDIA GALLI INFECTION IN NATIVE BIRDS - Thomas, K Shibi; Reetha, T Lurthu (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Traditional backyard poultry keeping with a flock size of 5-20 birds, with almost zero financial input is quite popular amongst rural population. The egg production through backyard system contributes to 30% of national egg production (Singh et al., 2009). Helminthiasis is considered as one of the most significant constraints on poultry production in humid tropical climatic conditions of parasites (Kulkarni et al., 2001).